Implementation Of Web-Based Guest Book Information System Using Agile Method At Pt. Syntax Corporation Indonesia - Aldo Hermaya Aditya Nur Karsa; Marsani Asfi; Suwandi Suwamdi (Green Publisher Indonesia, 2024)
The Guest Book Management Information System (SIPBT) plays a crucial role in digitalizing and enhancing the efficiency of guest recording processes. Implementing a web-based guest book system using Agile methods has proven effective in overcoming manual challenges and improving administrative processes. This study demonstrates the successful application of Agile methods in managing guest book systems. By utilizing a web-based system built with PHP, HTML, and the Laravel framework, the research achieved its goals effectively. The system provides administrators with easy management and monitoring of guest data, including a WhatsApp notification feature for efficient communication. The system also includes a user-friendly interface and webcam photo capture for easy guest identification, enhancing guest monitoring and search efficiency.